A method for measuring muscle strength in restraining valgus joint angulation: Elbow varus muscle strength against valgus loading - Onuma, K.; Yanai, T. (Journal of Biomechanics, 2023)
Skeletal muscle works as a dynamic joint stabilizer, assisting the underlying ligaments in restricting joint angulation by actively resisting external loads. Despite its clinical importance, little is known about the muscle strength required to produce torque to help ligaments restrict joint angulation within the physiological range permitted by the joint structure. In this study, we introduce a method for measuring the strength of the elbow musculature in restraining valgus angulation and present the values obtained in 20 healthy young men. Each participant was fastened to a Biodex dynamometer, with the elbow joint flexed to 90° and the varus-valgus axis aligned to the dynamometer`s rotation axis. Maximal voluntary isometric ramp contraction of shoulder internal rotators was performed while the humeroulnar joint gap was monitored with an ultrasound apparatus. The largest torque recorded while the humeroulnar joint gap did not exceed a predetermined individualized threshold was considered to be the elbow varus strength of the participant. The elbow varus strength of the dynamic stabilizer was found to be 41 ± 12 Nm, which agreed with the value estimated by our musculoskeletal model. The inter-operator reliability test indicated excellent reliability (ICC (2,1) = 0.91). These findings suggest that the present method is valid for measuring the strength of the elbow musculature in restraining the valgus angulation. Measurements of this aspect of strength are expected to provide insights for understanding and preventing elbow injuries.